Kajian Yuridis Terhadap Kegiatan Penanaman Modal Dalam Bidang Perhotelan Di Kabupaten Lombok Barat - Dwi Martini (Jatiswara, 2012)
This reseach is a normative – empirical type of reseach concerning “Legal study of direct investment related to hospitality business in Lombok Barat Regency”. This reseach is made to find out and analyze investment policies related to hospitality business existing in Lombok Barat regency and to find out the contribution of these policies to encourage the development of local investment. The reseach result shows that there are several Law and regulation existing as policies made by local government to rule direct investment specially hospitality business in their area such as local law, The decision of the head of the regency, The decision of the head of Investment coordinating body eventhought none of these policies specifically rule investment in hospitality business. Contributions of these policy to encourage the development of investment in hospitality business could be seen from the increase number of hospitality business investment year to year from year 2007-2011. Investment policy that formulated by local government has adjusted to Investment Law number 25 of 2007 concerning Investment such as the implementation of non-discrimination principle by giving an equal treatment toward domestic and foreign investment, mentioning the right, obligation and responsibility of the investors also giving investment facilities and incentives. In the other side it still necessarry to make some changes for the perfection of those local policies specially to shorten the bureaucracy line and to support the implementation of investment guidance, control and supervision.